Prolonged survival of Diamond-Blackfan anemia and RPS19 mutation: an observation in Togo - Padaro Essohana; Layibo Yao; M. C. Womey Kodzovi; Agbetiafa Kossi; Manang Hèzouwè; Mawussi Koffi; Irénée Kueviakoe; R. Agate Pikiliwé; Vovor Ahoefa (Journal of Hematology and Oncology Research, 2023)
Objective Drawing up a balance sheet of 16 years follow-up of the sole case of Diamond-Blackfan anemia diagnosed in Togo with arguments of molecular biology. Observation T.S a boy, born on 5th september 2006 has been followed up since he was three months, for Diamond-Blackfan anemia (DBA) in whom there has been found the mutation of ribosomial protein RPS19 in july 2010. It was the first observation in Subsaharian Africa. The treatment by transfusions from december 2006 to december 2022 has been associated with iron chelation through deferoxamin and promptly with corticotherapy at the dosage of 2mg/kg/day. The corticotherapy has been reduced as a consequence of corticoresistance from the fourth week, then definitely interrupted after four months. The evolution is marked by a clinical improvement with a staturo-balanced curve, and during the last control of 28th december 2022, the child was 53 kg heavy and 160 cm tall. The monthly physical tests did not reveal any signs of eventual overloading and the echocardiography of 26th december 2022 was normal. On the biological plan, the rate of the haemoglobin had been stable around 50g/l as a resultant of a transfusion each 4 to 6 weeks of red blood cell pellet. The chelation of iron had been done through deferoxamin with a monthly control of serum ferritin. That serum ferritin was 738,39ng/mg at diagnosis before the beginning of transfusions and during the follow-up, we noticed an average of 2977,3ng/ml (range 1817,1ng/ml and 4448,5ng/ml) Conclusion Thanks to the regular transfusions derived from the survey of the parameters of iron and the use of deferoxamin, we have succeded in keeping alive during sixteen years a patient who caught a disease whose evolution is unpredictable.
Keywords: Diamond-Blackfan anemia